Labour Jurisprudence - Dion, Denys (Relations industrielles / Industrial Relations, 1949)
In order to keep the readers of the Bulletin up-to-date, the Research Service is undertaking a monthly report of Labour Jurisprudence. In principle, this report will bear on current cases of jurisprudence whether in the Civil Courts, as the Superior Court or the Court of King's Bench, or in the arbitration courts, or again on the interesting decisions of the different Provincial and Federal administrative Commissions. We might even deal with particular decisions of the courts of other countries. Although our special aim will be to stick to current cases it will frequently happen that the report will refer to the past in order to present the reader with an analysis of cases which remain, in spite of the passage of time, of great current interest. We are very well aware that jurisprudence has its most solid sources in decisions which go a long way back.